Application of planar auto-compensating laser-induced incandescence to low-sooting turbulent flames and investigation of the detection gate width effect. Issue 11 (2nd November 2021) - Bouvier, M.; Yon, J.; Liu, F.; Cabot, G.; Grisch, F.
Abstract: Laser-induced incandescence (LII) is an optical technique that is widely used for the in situ measurement of the soot volume fraction in flames. The low intensity of LII signals in low-sooting turbulent flames means that long camera acquisition times are needed to achieve sufficiently high signal-to-noise ratios. The direct application of auto-compensating LII (AC-LII) to infer the soot volume fraction from the measured LII signals can lead to large errors due to the significant decrease in the temperature of the soot particles over the duration of the camera gate. In order to reduce the measurement errors from AC-LII, we propose an improved approach in which the cooling of soot particles during the camera acquisition of LII signals is considered. The proposed methodology is applied to planar AC-LII measurements for the determination of soot volume fraction and primary particle diameter in a low-sooting turbulent flame, with the help of the open source LII software LIISim. This study represents the first application of planar AC-LII to a turbulent flame. A sensitivity analysis is also conducted in order to determine the main factors affecting the uncertainty of the proposed approach. Copyright © 2021 American Association for Aerosol Research